2019
DOI: 10.1038/s41467-019-11774-w
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory landscape of a core maize domestication module controlling bud dormancy and growth repression

Abstract: Many domesticated crop plants have been bred for increased apical dominance, displaying greatly reduced axillary branching compared to their wild ancestors. In maize, this was achieved through selection for a gain-of-function allele of the TCP transcription factor teosinte branched1 ( tb1 ). The mechanism for how a dominant Tb1 allele increased apical dominance, is unknown. Through ChIP seq, RNA seq, hormone and sugar measurements on 1 mm axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
155
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(162 citation statements)
references
References 79 publications
6
155
1
Order By: Relevance
“…A recent genome-wide ChIP-seq assay reported that TB1 mainly binds to promoters, and only a few peaks were located within gene body regions 6 . In our study, TEN predominantly bound to the gene body, and this was not unexpected, given that these two genes have diverged over a significant period of evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent genome-wide ChIP-seq assay reported that TB1 mainly binds to promoters, and only a few peaks were located within gene body regions 6 . In our study, TEN predominantly bound to the gene body, and this was not unexpected, given that these two genes have diverged over a significant period of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a genome-wide binding profile uncovered a genetic pathway putatively regulated by TB1 6 . The study reported that TB1 binds mainly to promoters, with only a few peaks located within gene body regions.…”
mentioning
confidence: 99%
“…In isogenic double mutants of Oy1-N1989 allele with gt1 and tb1, vey1 locus that have been previously shown to cause gradual decline in photosynthetic capacity and sugar accumulation of Oy1-N1989 mutants (Khangura et al 2019b) also influenced tiller number in a vey1-dependent manner (Figure 10). A study analyzing young axillary buds of tb1 and gt1 mutants in maize found increased sugar biosynthesis and metabolism to be critical for breaking bud dormancy and that tb1 bound to the promoters of genes encoding enzymes important for energy sensing, such as enzymes involved in trehalose-6-phosphate metabolism (Dong et al 2019). Analysis of transcript abundance in axillary buds of tin1 variants found photosynthesis to be the most enriched gene ontology term and chlorophyll biosynthesis to be highly upregulated in non-dormant tiller buds (Zhang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of class II TCPs regulating plant form in crops; suppression of axillary meristem or tiller outgrowth in grasses by tb1 [25,75], lateral branch angle in maize tassels by wavy auricle on blade 1/ branch angle defective 1 (wab1/ bad1) [76,77], and floral symmetry in sunflower by HaCYC2 [78]. Recently, it was shown that a class II TCP, MULTISEEDED 1 (MSD1), regulates floral fertility and therefore grain number in sorghum, by mediating accumulation of jasmonic acid in the panicle [79].…”
Section: Discussionmentioning
confidence: 99%